2021
DOI: 10.3390/jcm10091971
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Liver Stiffness by Two-Dimensional Shear Wave Elastography and Waist Circumference in Japanese Local Citizens with Abdominal Obesity

Abstract: Background: Various factors other than fibrosis could affect liver stiffness (LS), measured by two-dimensional shear wave elastography (2D-SWE). We aimed to clarify the factors affecting LS in local citizens. Methods: We performed a cross-sectional study among local citizens of a health checkup program. Abdominal obesity was defined as waist circumference ≥85 cm for men and ≥90 cm for women. We evaluated the correlation between LS by 2D-SWE (Aplio 500) and waist circumference with linear regression analyses. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…MS is associated with high liver stiffness [ 115 ]. Moreover, a cross-sectional, one-center Japanese study in people with abdominal obesity (Japanese diagnostic criteria for MS include waist circumference values of ≥85 cm for men and ≥90 cm for women) showed that waist circumference was significantly and independently correlated with liver stiffness measured by 2D-SWE [ 116 ]. The advantages of 2D-SWE have become evident in individuals with NAFLD and severe obesity, where its findings showed a higher success rate in comparison with TE, one of the most validated tools available [ 117 ].…”
Section: Ultrasound-based Hepatic Shear Wave Elastographymentioning
confidence: 99%
See 1 more Smart Citation
“…MS is associated with high liver stiffness [ 115 ]. Moreover, a cross-sectional, one-center Japanese study in people with abdominal obesity (Japanese diagnostic criteria for MS include waist circumference values of ≥85 cm for men and ≥90 cm for women) showed that waist circumference was significantly and independently correlated with liver stiffness measured by 2D-SWE [ 116 ]. The advantages of 2D-SWE have become evident in individuals with NAFLD and severe obesity, where its findings showed a higher success rate in comparison with TE, one of the most validated tools available [ 117 ].…”
Section: Ultrasound-based Hepatic Shear Wave Elastographymentioning
confidence: 99%
“…F ≥ 3 represents advanced fibrosis, while the F4 fibrosis stage usually suggests cirrhosis [ 142 ]. Supplementary difficulties arise from some studies not reporting LSM cut-offs that define different fibrosis stages [ 57 , 72 , 91 ], while others use different stage appellations that are difficult to correlate with the current standard definitions [ 81 , 83 , 89 , 116 ]. The age-adapted cut-offs should also be taken into account to improve the method’s performance.…”
Section: Gaps In Knowledgementioning
confidence: 99%